2020
DOI: 10.1371/journal.pntd.0008898
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Lagos bat virus infection in straw-colored fruit bats: A suitable model for bat rabies in a natural reservoir species

Abstract: Rabies is a fatal neurologic disease caused by lyssavirus infection. Bats are important natural reservoir hosts of various lyssaviruses that can be transmitted to people. The epidemiology and pathogenesis of rabies in bats are poorly understood, making it difficult to prevent zoonotic transmission. To further our understanding of lyssavirus pathogenesis in a natural bat host, an experimental model using straw-colored fruit bats (Eidolon helvum) and Lagos bat virus, an endemic lyssavirus in this species, was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…Experimental infections (Table 6) have mostly been performed in non-reservoir hosts, such as mice, potentially resulting in inaccurate disease progression assumptions in naturally infected animals. More recently, the pathogenesis of LBV in one of its natural hosts, i.e., E. helvum, was investigated [63,64]. Similar mortality rates, as observed in other animals, were reported (Table 6).…”
Section: Pathogenesissupporting
confidence: 67%
See 4 more Smart Citations
“…Experimental infections (Table 6) have mostly been performed in non-reservoir hosts, such as mice, potentially resulting in inaccurate disease progression assumptions in naturally infected animals. More recently, the pathogenesis of LBV in one of its natural hosts, i.e., E. helvum, was investigated [63,64]. Similar mortality rates, as observed in other animals, were reported (Table 6).…”
Section: Pathogenesissupporting
confidence: 67%
“…The mechanisms of virus maintenance and transmission of lyssaviruses in bats are not well understood and could be influenced by various factors [2,26]. The experimental infection of E. helvum with LBV indicated that bats that survived the challenge had developed virus neutralizing antibodies (53%), suggesting that bats can develop an immune response without clinical disease development and thus not excrete virus [63]. This would support surveillance results, indicating high seroprevalence and low virus detection in Africa.…”
Section: Pathogenesismentioning
confidence: 53%
See 3 more Smart Citations